Reflections on taking and retaking of the Courthouse, and recent convictions to military officers involved in the retaking - Rafael Uribe, Semillero de investigación (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The research seedbed Rafael Uribe Uribe is an idea born of the absence of  unconventional intellectual production in Law and Social Sciences School from the UPTC, in order to claim this axiological essence, implicit in its name School of Law and Social Sciences, through ideal thesis upheld in the material practice of such knowledge. To this purpose it has initiated a research process based on the constitutional and legal guarantees that the state gives to exercise opposition from the 1991 Constitution, interpreting its and formal contexts. As a starting point and first step of research we analyze the facts occurred on 6 and 7 November 1985 in Bogota during the taking and retaking of the Courthouse perpetrated by the M-19, emphasizing the disappearance of the people who survived after the retaking by the Army, and the recent convictions of the soldiers involved in the disappearance, analyzing prospective convictions  from a criminal, constitutional, and comparative law from the legal argument especially based on the postulates of the school of judicial activism. We highlights the important role carried out by the judiciary that in a state and a democracy such as the Colombian, in performances like this, takes a so- called opposition status suffering victimization as a result of the objective performance of its duties.